2021
DOI: 10.1111/risa.13833
|View full text |Cite
|
Sign up to set email alerts
|

I Think, Therefore I Act: The Influence of Critical Reasoning Ability on Trust and Behavior During the COVID‐19 Pandemic

Abstract: Actively open‐minded thinking (AOT) operates in three dimensions: it serves as a norm accounting for how one should search for and use information in judgment and decision making; it is a thinking style that one may adopt in accordance with the norm; and it sets standards for evaluating the thinking of others, particularly the trustworthiness of sources that claim authority. With the first and third dimensions in mind, we explore how AOT influences trust in public health experts, risk perceptions, and complian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 64 publications
4
14
0
Order By: Relevance
“…Finally, when it comes to measures to prevent the spread of COVID‐19, the issue of people's trust is certainly a central one (Cohen et al., 2022; Siegrist, 2021). We did not measure this variable, but it is very likely to play a role and should be included in future studies testing our proposed model.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, when it comes to measures to prevent the spread of COVID‐19, the issue of people's trust is certainly a central one (Cohen et al., 2022; Siegrist, 2021). We did not measure this variable, but it is very likely to play a role and should be included in future studies testing our proposed model.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars suggested that people's lack of efficacy in performing the recommended behaviors could account for this case (Siegrist et al., 2021). Besides, studies on trust in authorities found mixed results regarding the influence of trust on people implementing or accepting protective measures and negative emotions like fear (Cohen et al., 2021; Siegrist et al., 2021; Wachinger et al., 2013). This study takes threat perception, efficacy perception, emotion, and behavioral strategies into account, synthetically demonstrating people's risk processing patterns when facing a pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Reasoning abilities, as measured by a variety of scales, are found to be strong predictors of accuracy in misinformation and fake news discernment (Ross et al, 2021), and agreement to climate arguments (McPhetres et al, 2019). Similarly, reasoning ability is related to health-related beliefs, such as vaccine attitudes, Coronavirus conspiracy beliefs, preventive behaviours such as hand washing and wearing masks (Čavojová et al, 2022), trust in public health experts and consequently, higher perceived risk of infection and compliance with CDC guidelines during COVID pandemic (Cohen et al, 2021).…”
Section: The Ideological Blindness Account: Challengesmentioning
confidence: 99%